2022
DOI: 10.3390/antiox11050826
|View full text |Cite
|
Sign up to set email alerts
|

Physical-Exercise-Induced Antioxidant Effects on the Brain and Skeletal Muscle

Abstract: Erythroid-related nuclear factor 2 (NRF2) and the antioxidant-responsive-elements (ARE) signaling pathway are the master regulators of cell antioxidant defenses, playing a key role in maintaining cellular homeostasis, a scenario in which proper mitochondrial function is essential. Increasing evidence indicates that the regular practice of physical exercise increases cellular antioxidant defenses by activating NRF2 signaling. This manuscript reviewed classic and ongoing research on the beneficial effects of exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 159 publications
0
8
0
Order By: Relevance
“…Thus, plasma and urinary Nep levels are dependent on macrophage activity [ 81 ]. This relationship has been clearly shown in studies of exercise and impact-induced injury during intense physical activity [ 82 ]. Urinary Nep and total Nep (Nep + H 2 Nep) levels are indicative of oxidative stress and trauma-induced inflammation [ 83 ].…”
Section: Different Oxidation States Relate To Different Biological Ro...mentioning
confidence: 77%
“…Thus, plasma and urinary Nep levels are dependent on macrophage activity [ 81 ]. This relationship has been clearly shown in studies of exercise and impact-induced injury during intense physical activity [ 82 ]. Urinary Nep and total Nep (Nep + H 2 Nep) levels are indicative of oxidative stress and trauma-induced inflammation [ 83 ].…”
Section: Different Oxidation States Relate To Different Biological Ro...mentioning
confidence: 77%
“…Notably, Gong et al have reported that nuclear factor erythroid 2‐related factor 2 (Nrf2) activation and RSPO3 promoter demethylation are the major drivers of RSPO3 expression in lung adenocarcinomas 50 . As a critical regulator of cellular defense against oxidative and inflammatory lesions, Nrf2 activation has been recognized as one of the key mechanisms responsible for the antioxidant and anti‐inflammatory capacities of regular physical exercise in a variety of tissues including lung, liver, brain, and kidney 19,51–53 . On the other hand, the benefits of exercise training in metabolic diseases, osteoporosis, and physical fitness have recently been shown to involve DNA demethylation of critical genes such as peroxisome proliferator‐activated receptor γ coactivator‐1α (Ppargc1a), 54,55 Nrf2, 56 and myogenic differentiation 1 (MYOD1) 57 .…”
Section: Discussionmentioning
confidence: 99%
“…50 As a critical regulator of cellular defense against oxidative and inflammatory lesions, Nrf2 activation has been recognized as one of the key mechanisms responsible for the antioxidant and anti-inflammatory capacities of regular physical exercise in a variety of tissues including lung, liver, brain, and kidney. 19,[51][52][53] On the other hand, the benefits of exercise training in metabolic diseases, osteoporosis, and physical fitness have recently been shown to involve DNA demethylation of critical genes such as peroxisome proliferator-activated receptor γ coactivator-1α (Ppargc1a), 54,55 Nrf2, 56 and myogenic differentiation 1 (MYOD1). 57 These findings raise the possibility that Nrf2 activation and DNA demethylation may be involved in aerobic exercise-induced RSPO3 expression in the kidney, which merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, non-pharmacological therapies that aim to regulate the redox balance should alleviate the nonspeci c signaling of ROS while promoting the reduction of oxidative processes, such as lipoperoxidation and protein and DNA oxidation/modi cation [34]. Brain sensitivity to oxidative stress negatively affects the levels of proteins involved in metabolism and cerebral neuroprotection [28,35]. ampli ed by kinase cascade activation or can be transmitted over long distances by conversion to more stable species, such as lipid peroxides, and has high concentrations in the extracellular environment.…”
Section: Discussionmentioning
confidence: 99%